Industry 4.0 Readiness Trends: A Bibliometric and Visualization Analysis - Solikhah, Efa Wakhidatus; Asih, Hayati Mukti; Astuti, Fatma Hermining; Ghazali, Ihwan; Mohammad, Effendi Bin (Association for Scientific Computing Electronics and Engineering (ASCEE), 2024)
The Industrial Revolution 4.0 signifies a pivotal change in industrial paradigms, integrating advanced technologies like the Internet of Things (IoT), artificial intelligence (AI), robotics, and big data into production processes. This research aims to analyze the growth and readiness in industry for these changes through a detailed bibliometric analysis. It quantitatively tracks the expansion of Industry 4.0 readiness research, including publication counts, citation trends, and thematic shifts, reflecting heightened academic and industrial interests. A clear definition of Industry 4.0 readiness is provided, focusing on metrics and criteria used for assessment. The paper identifies key contributions and novel insights of the research, emphasizing its practical implications for industry and academia. It examines elements influencing Industry 4.0 readiness, such as infrastructure, policy, and workforce preparedness, offering a comprehensive overview of challenges. The practical implications of our findings are presented, suggesting actionable strategies for stakeholders. This research also highlights the gaps in the current literature, which offers a thorough and multidimensional understanding of Industry 4.0 readiness, its influences, and its impact on the global industrial system.